Exclusive central diffractive production of scalar and pseudoscalar mesons: tensorial vs. vectorial pomeron - Lebiedowicz, Piotr; Nachtmann, Otto; Szczurek, Antoni (Annals of physics, 2014)
We discuss consequences of the models of “tensorial pomeron” and “vectorial pomeron” for exclusive diffractive production of scalar and pseudoscalar mesons in proton-proton collisions. Diffractive production of f0(980), f0(1370), f0(1500), η, and η′(958) mesons is discussed. Different pomeron-pomeron-meson tensorial coupling structures are possible in general. In most cases two lowest orbital angular momentum-spin couplings are necessary to describe experimental differential distributions. For f0(980) and η production reggeon-pomeron, pomeron-reggeon, and reggeon-reggeon exchanges are included in addition, which seems to be necessary at relatively low energies. The theoretical results are compared with the WA102 experimental data. Correlations in azimuthal angle between outgoing protons, distributions in rapidities and transverse momenta of outgoing protons and mesons, in a special “glueball filter variable”, as well as some two-dimensional distributions are presented. We discuss differences between results of the vectorial and tensorial pomeron models. We show that high-energy central production, in particular of pseudoscalar mesons, could provide crucial information on the spin structure of the soft pomeron.
Gesehen am 02.09.2020